Kontribusi Budaya Organisasi, Etos Kerja, Motivasi Kerja, dan Disiplin Kerja Terhadap Kinerja Pegawai di Lingkungan Rektorat Universitas Pendidikan Ganesha - N. Mudana; A.A.G. Agung; I.M. Yudana (Pascasarjana Universitas Pendidikan Ganesha, 2021)
This study aims to determine the Contribution of Organizational Culture, Work Ethic, Work Motivation, and Work Discipline on Employee Performance in the Rectorate of Ganesha University of Education. This study is an “ex-post facto” study with a sample size of 124 people. Data collection using a questionnaire. Analysis of research data using inferential statistics with simple regression techniques, partial correlation, and multiple regression. The results showed that: (1) there was a significant contribution of organizational culture to performance, with a contribution of 80.3%, a correlation coefficient of 0.896, and an effective contribution of 22.84%; (2) there is a significant contribution of work ethic to performance, with a contribution of 97.1%, a correlation coefficient of 0.985 and an effective contribution of 18.13%; (3) there is a significant contribution of work motivation to performance, with a contribution of 61, 6%, the correlation coefficient is 0.785 and the effective contribution is 15.22%; (4) there is a significant contribution of work discipline to performance, with a contribution of 63.4%, a correlation coefficient of 0.796 and an effective contribution of 12.43%; and (5) collectively, there is a significant contribution to organizational culture, ethos. work, work motivation, and work discipline on employee performance in the Ganesha University of Education Rectorate, with a multiple correlation coefficient of 0.828, and a contribution of 68.62%